Extracellular gentamicin reduces the activity of connexin hemichannels and interferes with purinergic Ca2+ signaling in HeLa cells - Figueroa, Vania A.; Retamal, Mauricio A.; Cea, Luis A.; Salas, José D.; Vargas, Aníbal A.; Verdugo, Christian A.; Jara, Oscar; Martínez, Agustín D.; Sáez, Juan C. (Frontiers in Cellular Neuroscience, 2014)
Gap junction channels (GJCs) and hemichannels (HCs) are composed of protein subunits termed connexins (Cxs) and are permeable to ions and small molecules. In most organs, GJCs communicate the cytoplasm of adjacent cells, while HCs communicate the intra and extracellular compartments. In this way, both channel types coordinate physiological responses of cell communities. Cx mutations explain several genetic diseases, including about 50% of autosomal recessive nonsyndromic hearing loss. However, the possible involvement of Cxs in the etiology of acquired hearing loss remains virtually unknown. Factors that induce post-lingual hearing loss are diverse, exposure to gentamicin an aminoglycoside antibiotic, being the most common. Gentamicin has been proposed to block GJCs, but its effect on HCs remains unknown. In this work, the effect of gentamicin on the functional state of HCs was studied and its effect on GJCs was reevaluated in HeLa cells stably transfected with Cxs. We focused on Cx26 because it is the main Cx expressed in the cochlea of mammals where it participates in purinergic signaling pathways. We found that gentamicin applied extracellularly reduces the activity of HCs, while dye transfer across GJCs was not affected. HCs were also blocked by streptomycin, another aminoglycoside antibiotic. Gentamicin also reduced the ATP release and the HC-dependent oscillations of cytosolic free-Ca2+ signal. Moreover, gentamicin drastically reduced the Cx26 HC-mediated membrane currents in Xenopus laevis oocytes. Therefore, the extracellular gentamicin-induced inhibition of Cx HCs may adversely affect autocrine and paracrine signaling, including the purinergic one, which might partially explain its ototoxic effects.